PERAN KOPERASI SYARIAH DALAM MENINGKATKAN PEREKONOMIAN DI PONDOK PESANTREN IMAM ASY- SYAFI’I BREBES - Raihan, Muhammad (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study aims to analyze the role of Islamic cooperatives in enhancing the economy at the Imam Asy-Syafi’i Islamic Boarding School in Brebes. Employing a descriptive qualitative approach, data were collected through interviews, observations, and document analysis. The findings reveal that the Islamic cooperative plays a vital role in centrally fulfilling students' needs, empowering the local community through a consignment system, and applying Islamic economic principles in its operations. The policy prohibiting students from private trading fosters economic discipline focused on education and character development. Although the cooperative has shown success in many aspects, it still faces major challenges such as limited capital, managerial capacity, and market access. Therefore, institutional strengthening and strategic business development are needed to ensure the cooperative's sustainability and replication in other pesantren as a model of sharia-based economic empowerment